Achieving all-age helmet use compliance for snow sports: strategic use of education, legislation and enforcement. Issue 3 (9th December 2015) - Fenerty, Lynne; Heatley, Jennifer; Young, Julian; Thibault-Halman, Ginette; Kureshi, Nelofar; Bruce, Beth S; Walling, Simon; Clarke, David B
Abstract : Background: Nova Scotia is the first jurisdiction in the world to mandate ski and snowboard helmet use for all ages at ski hills in the province. This study represents a longitudinal examination of the effects of social marketing, educational campaigns and the introduction of helmet legislation on all-age snow sport helmet use in Nova Scotia. Methods: A baseline observational study was conducted to establish the threshold of ski and snowboarding helmet use. Based on focus groups and interviews, a social marketing campaign was designed and implemented to address factors influencing helmet use. A prelegislation observational study assessed the effects of social marketing and educational promotion on helmet use. After all-age snow sport helmet legislation was enacted and enforced, a postlegislation observational study was conducted to determine helmet use prevalence. Results: Baseline data revealed that 74% of skiers and snowboarders were using helmets, of which 80% were females and 70% were males. Helmet use was high in children (96%), but decreased with increasing age. Following educational and social marketing campaigns, overall helmet use increased to 90%. After helmet legislation was enacted, 100% compliance was observed at ski hills in Nova Scotia. Conclusions: Results from this study demonstrate that a multifaceted approach, including education, legislation and enforcement, was effective in achieving full helmet compliance among all ages of skiers and snowboarders.